ANALISIS KARAKTERISTIK DAN KOMPLIKASI PASIEN DIABETES MELITUS TIPE 1 DAN TIPE 2 DI RUANG RAWAT INAP RSUD KOTA DUMAI TAHUN 2016 - Sartika, Linda "; Utomo, Wasisto "; Karim, Darwin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractDiabetes Mellitus (DM) is one of metabolic diseases, recognized by hyperglycemia that occurs due to insulin secretion abnormality, insulin performance abnormality, or both of them. The number of patients with Diabetes Mellitus Type 1 and Type 2 that hospitalized in Dumai City Hospital Wards are increasing every year with various cases includes : acute and chronic complications of macrovascular and microvascular. This research was a quantitative study using descriptive retrospective approach. The study aimed to describe the analysis of characteristics and complications among patients with Diabetes Mellitus Type 1 and Type 2 who were hospitalized in the Dumai City Hospital Wards. As many as 315 respondents participated in this study using total sampling technique. Data were collected using work sheet that prepared by the author. The result shown that majority of respondents experienced acute complications with hyperglycemia, as many as 89 patients (23,8%). Chronic microvascular complications were dominated by patients with nephropathy, as many as 61 patients (19.4%). While majority of chronic macrovascular complication was cerebrovascular disease, as many as 32 patients (10.2%).  This study recommends health staffs, especially nurses to increase their roles to support the patients in order to reduce complications of Diabetes Mellitus Type 1 and Type 2.  Keywords: Analysis, Diabetes Mellitus (DM),  microvaskular complications,  macrovaskular complications